(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study aimed to inspect the occurrence of Haemoproteus tinnunculi (H. tinnunculi) in falcons from the central area of Saudi Arabia. Materials and Methods: Blood samples from 100 falcons species, including 55 Falco cherrug, 22 Falco peregrinus, 13 Falco pelegrinoides, and 10 Falco rusticolus, were collected from November 2018 to April 2019 and examined for H. tinnunculi by microscopic examination and nested PCR, targeting a cytochrome b (cytb) gene. Results: The prevalence was 1% by microscopic examination. The prevalence rate of H. tinnunculi was 1% by the microscopic method and 3% by PCR. Only F. cherrug was infected. In the sequence and phylogenetic analyses, the two cytb H. tinnunculi sequences were 100% identical and closely related to the Lithuanian isolate with 99.35% identity. Conclusions: This study presents the first report of molecular detection and characterization of H. tinnunculai in F. cherrug from the Kingdom of Saudi Arabia. J. Adv. Vet. Anim. Res., 7(4): 626-632, Dec 2020 http://doi.org/10.5455/javar.2020.g461